Wave Equation Show that

\[

$u(x, t)=\frac{1}{2}[f(x-c t)+f(x+c t)]$

\]

is a solution to the one-dimensional wave equation $\frac{\partial^{2} u}{\partial t^{2}}=c^{2} \frac{\partial^{2} u}{\partial x^{2}} .$

(This equation describes the small transverse vibration of an elastic string such as those on certain musical instruments.)

\[

$u(x, t)=\frac{1}{2}[f(x-c t)+f(x+c t)]$

\]

is a solution to the one-dimensional wave equation $\frac{\partial^{2} u}{\partial t^{2}}=c^{2} \frac{\partial^{2} u}{\partial x^{2}} .$

(This equation describes the small transverse vibration of an elastic string such as those on certain musical instruments.)

Community Answer

Honor CodeSolved 1 Answer

See More Answers for FREE

Enhance your learning with StudyX

Receive support from our dedicated community users and experts

See up to 20 answers per week for free

Experience reliable customer service

Get Started

u(x, t)=\frac{1}{2}[f(x-c t)+f(x+c t)]Let r=x-c t and s=x+c t.\begin{array}{l}\text { Then } u(r, s)=\frac{1}{2}[f(r)+f(s)] \\\frac{\partial u}{\partial t}=\frac{\partial u}{\partial r} \frac{\partial r}{\partial t}+\frac{\partial u}{\partial s} \frac{\partial s}{\partial t}=\frac{1}{2} \frac{d f}{d r}(-c)+\frac{1}{2} \frac{d f}{d s}(c) \\\frac{\partial^{2} u}{\partial t^{2}}=\frac{1}{2} \frac{d^{2} f}{d r^{2}}(-c)^{2}+\frac{1}{2} \frac{d^{2} f}{d s^{2}}(c)^{2}=\frac{c^{2}}{2}\left[\frac{d^{2} f}{d r^{2}}+\frac{d^{2} f}{d s^{2}}\right] \\\frac{\partial u}{\partial x}=\frac{\partial u}{\partial r} \frac{\partial r}{\partial x}+\frac{\partial u}{\partial s} \frac{\partial s}{\partial x}=\frac{1}{2} \frac{d f}{d r}(1)+\frac{1}{2} \frac{d f}{d s}(1) \\\frac{\partial^{2} u}{\partial x^{2}}=\frac{1}{2} \frac{d^{2} f}{2 d r^{2}}(1)^{2}+\frac{1}{2} \frac{d^{2} f}{d s^{2}}(1)^{2}=\frac{1}{2}\left[\frac{d^{2} f}{d r^{2}}+\frac{d^{2} f}{d s^{2}}\right]\end{array}So, \frac{\partial^{2} u}{\partial t^{2}}=c^{2} \frac{\partial^{2} u}{\partial x^{2}} ...